2018
DOI: 10.19153/cleiej.21.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Towards Technological Approaches for Concept Maps Mining from Text

Abstract: Concept maps are resources for the representation and construction of knowledge. They allow showing, through concepts and relationships, how knowledge about a subject is organized. Technological advances have boosted the development of approaches for the automatic construction of a concept map, to facilitate and provide the benefits of that resource more broadly. Due to the need to better identify and analyze the functionalities and characteristics of those approaches, we conducted a detailed study on technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
3
0
4
Order By: Relevance
“…Devido à necessidade de melhor identificar e analisar as funcionalidades e características inerentes à questão de investigação, realizamos um estudo detalhado sobre abordagens tecnológicas para construção automática de mapas conceituais publicados entre 1994 e 2016 nas bases de dados IEEE Xplore, ACM e Elsevier Science Direct. A partir desse estudo, elaboramos uma categorização definida em duas perspectivas, Fonte de Dados e Representação Gráfica, contendo 14 categorias, detalhada em (Aguiar, Cury, & Zouaq, 2018). O estudo selecionou 30 artigos relevantes, que foram aplicados à categorização proposta para identificar os principais aspectos e limitações de cada abordagem.…”
Section: Método De Pesquisaunclassified
See 3 more Smart Citations
“…Devido à necessidade de melhor identificar e analisar as funcionalidades e características inerentes à questão de investigação, realizamos um estudo detalhado sobre abordagens tecnológicas para construção automática de mapas conceituais publicados entre 1994 e 2016 nas bases de dados IEEE Xplore, ACM e Elsevier Science Direct. A partir desse estudo, elaboramos uma categorização definida em duas perspectivas, Fonte de Dados e Representação Gráfica, contendo 14 categorias, detalhada em (Aguiar, Cury, & Zouaq, 2018). O estudo selecionou 30 artigos relevantes, que foram aplicados à categorização proposta para identificar os principais aspectos e limitações de cada abordagem.…”
Section: Método De Pesquisaunclassified
“…A Descrição da Fonte de Dados caracteriza um documento D. Um documento D de tamanho n pode ser definido como D = {d1...dn} onde di, i=1…,n é um termo em D. A definição de um processo de construção de mapa conceitual está relacionada à fonte de dados que será usada como fonte para extração do mapa. Nesse contexto, identificamos variações nas abordagens no que se refere ao tamanho (pequeno, regular e longo) e quantidade (único e conjunto de documentos) de informações disponíveis na fonte de dados, detalhadas e classificadas em (Aguiar, Cury, & Zouaq, 2018).…”
Section: Processo De Mineração De Mapas Conceituaisunclassified
See 2 more Smart Citations
“…Despite these advances, the automatic generation of CMs from unstructured text remains a significant challenge. Unsurprisingly, a secondary study by [Aguiar et al 2016] identified several techniques and proposed one to assist in automatically constructing CMs from unstructured texts. These processes usually involve semantic markings, followed by complex processing to identify and extract the elements present in the text.…”
Section: Introductionmentioning
confidence: 99%